Effects of two different short-term training programs on the physical and technical abilities of adolescent basketball players - Bogdanis, G.C.b; Ziagos, V.a; Anastasiadis, M.a; Maridaki, M.b (Journal of Science and Medicine in Sport, 2007)
{This study evaluated and compared the effectiveness of two different off-season, short-term basketball training programs on physical and technical abilities of young basketball players. Twenty-seven adolescent basketball players (14.7 ± 0.5 years; Tanner stage: 3.5 ± 0.5) were randomly divided into a specialized basketball training group (SP